Assessment of the LeadCare® Plus for Use on Scandinavian Brown Bears (Ursus arctos) - Boesen, Amanda H.; Thiel, Alexandra; Fuchs, Boris; Evans, Alina L.; Bertelsen, Mads F.; Rodushkin, Ilia; Arnemo, Jon M. (Frontiers in Veterinary Science, 2019)
Lead (Pb) exposure is associated with adverse health effects in both humans and wildlife. Blood lead levels (BLL) of sentinel wildlife species can be used to monitor environmental lead exposure and ecosystem health. BLL analysers, such as the LeadCare®, are validated for use in humans, assessed for use in some avian species and cattle, and are increasingly being used on wildlife to monitor lead exposure. The LeadCare® analysers use a technique called anodic stripping voltammetry (ASV). Species-specific conversion equations have been proposed to approximate the levels found with gold standard measuring methods such as inductively coupled plasma mass spectrometry (ICP-MS) because the ASV method has been shown to underestimate BLL in some species. In this study we assessed the LeadCare® Plus (LCP) for use on Scandinavian brown bears (Ursus arctos). LCP measurements were correlated with ICP-MS with a Bland-Altman analysed bias of 16.3 – 22.5%, showing a consistent overestimation of BLL analysed with LCP. Based on this analysis we provide conversion equations for calculating ICP-MS blood lead levels based on the LCP results in Scandinavian brown bears. Our study shows that the LeadCare® Plus can be used for monitoring of lead exposure by approximating gold standard levels using conversion equations. This enables comparison with other gold standard measured lead levels within the observed range of this study (38.20 – 174.00 µg/L). Our study also found that Scandinavian brown bears are highly exposed to environmental lead.